2020
DOI: 10.3390/cancers12113150
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate Inhibits Growth of Sunitinib-Resistant Renal Cell Carcinoma Cells through Cell Cycle Arrest and Induction of Ferroptosis

Abstract: Although innovative therapeutic concepts have led to better treatment of advanced renal cell carcinoma (RCC), efficacy is still limited due to the tumor developing resistance to applied drugs. Artesunate (ART) has demonstrated anti-tumor effects in different tumor entities. This study was designed to investigate the impact of ART (1–100 µM) on the sunitinib-resistant RCC cell lines, Caki-1, 786-O, KTCTL26, and A-498. Therapy-sensitive (parental) and untreated cells served as controls. ART’s impact on tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 83 publications
1
70
0
Order By: Relevance
“…Lack of studies also increases the risk of unidentified contraindications and adverse side effects of the natural compounds combined with conventional therapy [ 14 ]. However, some studies have been carried out indicating antitumor effects of natural compounds, notably if applied together with an established therapy or by counteracting therapy resistance [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of studies also increases the risk of unidentified contraindications and adverse side effects of the natural compounds combined with conventional therapy [ 14 ]. However, some studies have been carried out indicating antitumor effects of natural compounds, notably if applied together with an established therapy or by counteracting therapy resistance [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that promotion of ferroptosis could be exploited to treat cancer, and ferroptosis inducers exhibited great potential to improve therapeutic performance [16,19] . For instance, Markowitsch et al have demonstrated that artesunate could inhibit growth of sunitinib-resistant renal cell carcinoma cells through cell cycle arrest and induction of ferroptosis [20] . Sulfasalazine, a system xc-inhibitor, could inhibit cysteine uptake and lead to ferroptosis of glioma cells [21] .…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence that ART can exert anticancer effects on several types of cancer cells (6,15). ART has been reported to induce apoptosis, differentiation and autophagy in colorectal cancer cells by impairing angiogenesis (27), inhibiting cell invasion and migration (28), inducing cell cycle arrest (11), upregulating ROS levels, regulating signal transduction [for example, activating the AMPK-mTOR-Unc-51-like autophagy activating kinase (ULK1) pathway in human bladder cancer cells] (9) and blocking immune escape (29). In addition, ART has been shown to restore the sensitivity of a number of cancer types to chemotherapeutic drugs by modulating various signaling pathways; for example, ART can improve the apoptosis of HCC by inhibiting the PI3K/AKT/mTOR pathway (30), and can increase liver cancer cell sensitivity to sorafenib via suppression of the MEK/ERK pathway (31) (Fig.…”
Section: Anticarcinogenic Mechanism Of Artmentioning
confidence: 99%
“…ART inhibits the proliferation of bladder cancer cells (RT4, RT112, T24 and TCCSup), which is associated with G 0 /G 1 -phase cell cycle arrest and downregulation of cell cycle regulatory proteins [cyclin D1 and CDK4 (required for entry into the G 1 phase); CDK1 and cyclinA/B (essential during the late S phase and early M phase)] (10). ART can block cell cycle progression and lead to a significant reduction in the levels of the cell cycle activating proteins cyclin A, cyclin B, and CDK1, evoking G 0 /G 1 phase arrest and inhibiting growth of the cells in renal cell carcinoma (11). In breast cancer cells (MCF-7 and MDA-MB-231), ART can block G 2 /M progression by upregulating beclin-1 expression, which promotes autophagy (53).…”
Section: Cell Cycle Arrestmentioning
confidence: 99%
See 1 more Smart Citation